PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH DI KELAS X MAN 4 MARTUBUNG MEDAN - Anugrah Mulia Tampubolon (State Islamic University of North Sumatra, 2018)
The purpose of this research was to identify the inprovement of student's communication ability as an impact of problem based learnin, asd to find the interaction between the instructional approach and gender with improvement of student's communication ability. This research wasa quasy experiment with the sample of research was 70 students, consisted of X-IPA2 with 35 students asan experiment class and X-IPA4 with 35 students as a control class. The data which collected in this research were communication ability. The instruments which used to collect the data were a test of communication ability. The data were analyzed by using two way anava in the SPSS program. Based on the result of this research, it could be concluded that the improvement student's communication ability by using problem based learning better than improvemet student's communication ability by using a usuall learning. There was not an interaction between the instructional approach and gender with improvement student's communication ability